2022
DOI: 10.1097/gox.0000000000004208
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Infection in Implant-based Breast Reconstruction: Evaluating the Evidence for Common Practices and Standardized Protocols

Abstract: Background: Infection following implant-based breast reconstruction (IBBR) results in increased rates of hospital readmission, reoperation, patient and hospital expenses, and reconstructive failure. IBBR is a complex, multistep procedure, and there is a relative lack of high-quality plastic surgery evidence regarding "best practices" in the prevention of implant infections. In the absence of strong data, standardizing procedures based on available evidence can reduce error and improve efficacy and outcomes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Overall infection rate was significantly lower in the protocol group compared with the retrospective group (8.7% versus 17.0%; P < 0.05). The median postoperative day (POD) of infection diagnosis was 30 (range, 6-162) in the retrospective group, compared with 17.5 (range, [13][14][15][16][17][18][19][20][21] in the protocol group. When the infection outcome was dichotomized, protocol patients tended toward a lower rate of both minor (2.9% versus 5.7%; P = 0.99) and major (5.8% versus 11.3%; P = 0.09) infections, although this did not reach statistical significance in these modest subsamples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall infection rate was significantly lower in the protocol group compared with the retrospective group (8.7% versus 17.0%; P < 0.05). The median postoperative day (POD) of infection diagnosis was 30 (range, 6-162) in the retrospective group, compared with 17.5 (range, [13][14][15][16][17][18][19][20][21] in the protocol group. When the infection outcome was dichotomized, protocol patients tended toward a lower rate of both minor (2.9% versus 5.7%; P = 0.99) and major (5.8% versus 11.3%; P = 0.09) infections, although this did not reach statistical significance in these modest subsamples.…”
Section: Resultsmentioning
confidence: 99%
“…As part of a department-sponsored quality improvement initiative, the senior author led the design of an evidence-based, standardized protocol for IBBR at our institution. The design of the protocol was based upon the best available evidence from plastic surgery and other specialty literature, which has been summarized in a comprehensive evidence review by our group, 16 as well as previously published protocols shown to reduce implant infections. The decision to include specific interventions in the protocol was based upon expectation of efficacy as well as feasibility within our own institutional framework.…”
Section: Evidence-based Protocol Developmentmentioning
confidence: 99%
“…Much of the more recent literature supports evidence that there is no added benefit to an extended course of perioperative antibiotics in implant-based breast reconstruction. [26][27][28] However, it is well known that risk of wound complications and reconstruction failure is increased in patients with a higher BMI. [29][30][31] The odds of complications is shown to increase by 5.9% for every unit increase in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The MICAP, AICAP, LICAP, or LTAP flaps were then raised as previously described. 5 After placement of the flaps into the lumpectomy bed and closing the donor site, patients were sat up for evaluation. If additional volume was necessary, different BioZorb sizers (ranging from 2 cm × 2 cm to 4 cm × 5 cm) were placed to fill the defect.…”
Section: Methodsmentioning
confidence: 99%
“…We use the same protocol here to prevent biofilm contamination and infection as we do when performing implant-based postmastectomy reconstruction. 5 Drains were placed into the lumpectomy bed and removed within 1 week. Patient satisfaction with outcomes was assessed using a five-point Likert scale at a minimum of 11 months after surgery (1 = strongly disagree, 2 = disagree, 3 = undecided, 4 = agree, 5 = strongly agree) for the following questions:…”
Section: Methodsmentioning
confidence: 99%